IBN SINA’S THEORY OF THE SOUL AND ITS RELEVANCE TO ISLAMIC EDUCATION - Mu’arofah, Ulfiatul; Mustofa, Mohammad Hasan (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
A person who is known as a very influential figure in the East and West is Ibn Sina or better known as Avicenna in the Western world. The real contribution of Ibn Sina which has now developed is in terms of logic, metaphysics, physics, politics, ethics and the human spirit or psychology. In this research, he tries to explain his theory regarding the human soul or personality which can also be interpreted as psychological. The system is built on the foundation, first, by briefly describing the biography of Ibn Sina and the works and themes that are his main focus. Second, interpreting Ibn Sina's ideas regarding the human soul or psychology. Third, explore the correlation between Ibn Sina's ideas and Islamic education today. In the end, I hope that this brief description of this great figure can be an explanation and his views become a science that can be used.